A glucokinase-linked sensor in the taste system contributes to glucose appetite - Sandrine Chometton; A-Hyun Jung; Lilly Mai; Taylor Dal Bon; Alexa Osorio Ramirez; David W. Pittman; Lindsey A. Schier (Elsevier, 2022)
Objectives: Dietary glucose is a robust elicitor of central reward responses and ingestion, but the key peripheral sensors triggering these orexigenic mechanisms are not entirely known. The objective of this study was to determine whether glucokinase, a phosphorylating enzyme with known glucosensory roles, is also expressed in taste bud cells and contributes to the immediate hedonic appeal of glucose-containing substances. Methods and results: Glucokinase (GCK) gene transcripts were localized in murine taste bud cells with RNAScope®, and GCK mRNA was found to be upregulated in the circumvallate taste papillae in response to fasting and after a period of dietary access to added simple sugars in mice, as determined with real time-qPCR. Pharmacological activation of glucokinase with Compound A increased primary taste nerve and licking responses for glucose but did not impact responsivity to fructose in naïve mice. Virogenetic silencing of glucokinase in the major taste fields attenuated glucose-stimulated licking, especially in mice that also lacked sweet receptors, but did not disrupt consummatory behaviors for fructose or the low-calorie sweetener, sucralose in sugar naïve mice. Knockdown of lingual glucokinase weakened the acquired preference for glucose over fructose in sugar-experienced mice in brief access taste tests. Conclusions: Collectively, our data establish that glucokinase contributes to glucose appetition at the very first site of nutrient detection, in the oral cavity. The findings expand our understanding of orosensory inputs underlying nutrition, metabolism, and food reward.